Development of a muscle fatigue index for motorcyclist in prolonged riding / Muhammad Adzri Adzman ... [et al.] - Adzman, Muhammad Adzri; Omar, Abdul Rahman; Rashid, Helmi; Ma'arof, Muhammad Izzat Nor (2014)
For prolonged motorcycling, it is very common for motorcyclist to experience physiological discomfort such as muscle numbness or strain. These symptoms are known as muscle fatigue and upon continuous occurrences may lead to road accident as reported by a study. Muscle fatigue could be described as a condition where the ability of the skeletal muscle system to exert maximum action is reduced. The objective of this study was to establish a new index system to evaluate muscle fatigue. In determining motorcyclist’s perception towards discomfort that leads to muscle fatigue during prolonged motorcycling, survey research using questionnaire tool were performed among the undergraduate students from the Faculty of Mechanical Engineering, Universiti Teknologi MARA Shah Alam. The questionnaires were analyzed via Statistical Package Service and Solution (SPSS) with the level of confidence of 95% (1.96), expected proportion of 0.5 and the precision at 0.1. From the questionnaires, a specialized discomfort rating index system of various body regions for motorcycling named Motorcycling Fatigue Hazard Scale (MoFaHS) was established. The index system allows for the muscle fatigue evaluation of most major body region which are affected during motorcycling to be performed. The following body regions were identified to be the most severely affected (high muscle fatigue rating index): (i) neck/shoulder, (ii) forearm, (iii) upper back, and (iv) lower back. From here, the muscle activities of selected muscles that best represent these body regions were further analyzed via surface electromyography (sEMG) measurement. The data were tabulated and published in two International Ergonomics Conferences as chapter in books. The sEMG measurements were performed on a newly established, filed for patent and award winning Postura Motergo motorcycle test rig setup (bronze medal in the Invention, Innovation and Design Exposition 2014 (IIDEX2014)). With the establishment of the MoFaHS, muscle fatigue could now be quantitatively evaluated.